Development of Flipbooks-Based E-Book Media Based to Improve Learning Outcomes for IV Mathematics Subjects on Plane Structures in Elementary Schools - Purida, Adifa Ramadhea; Annisa, Choirul; Kartikasari, Apriliyani Diah; Tanti, Yusi Krisma (Proceeding International Conference on Education, 2024)
Instructional media are tools used by teachers or educators to facilitate the learning process. Visual media is often used. Therefore, researchers develop e-book media based on flipbooks in the learning process. The research objectives are: (1) to analyse the development of flipbook-based e-book media, (2) to assess the eligibility of flipbook-based e-book media in improving student outcomes, and (3) to evaluate the effectiveness of this media in enhancing student learning outcomes. Types of research used is the study Research and Development (R&D) with ADDIE research model. This research was held at Madrasah Ibtidaiyah with a total of 30 participants. This research result shows that, (1) the development of e-book media based on flipbooks using the ADDIE development model with 5 stages. (2) media suitability is determined by the results data. Validation media expert 1 of 98.3% with description "very worthy", media expert 2 stage II is 100% with the description "very worthy". Material expert 1 is 95% with the description “very worthy” and expert material 2 is 100% with “very worthy” statement. (3) Improvement in learning outcomes is observed through pre-test and post-test data, analysed using the N-Gain calculation. N-Gain percent show gained 63.84 with criteria “sufficiently effective”.